2022
DOI: 10.1155/2022/4541450
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Taguchi and Genetic Algorithm Techniques for Prediction of Optimal Part Dimensions for Polymeric Biocomposites in Fused Deposition Modeling

Abstract: Additive manufacturing has gained popularity among material scientists, researchers, industries, and end users due to the flexible, low cost, and simple manufacturing process. Among number of techniques, fused deposition modeling (FDM) is the most recognized technology due to easy operation, lower environmental degradation, and portable apparatus. Despite numerous advantages, the limitations of this technique are poor surface finish, dimensional accuracy, and mechanical strength, which must be improved. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…We observed that the size of WMP particles differs and varies as per the range stated earlier. This distribution was also observed to be almost homogeneous to comply with the mixing phenomena that was performed during the fabrication [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…We observed that the size of WMP particles differs and varies as per the range stated earlier. This distribution was also observed to be almost homogeneous to comply with the mixing phenomena that was performed during the fabrication [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 82%
“…This happened due to the high load bearing capability of both basalt and WMP. WMP acted as a connecting chain between the basalt fibre and epoxy resin promoting transfer of stress, which led to high deformation before fracture [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Moreover, large amount of dislocation formation due to the inclusion of WMP in the composite resulted in higher energy absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it played a pivotal role in optimizing a myriad of process parameters. These encompassed layer thickness [66][67][68][69], orientation angle [66,67,69], raster angle [66,67,69], raster width [66,67,69], printing temperature [68], infill pattern [68], slice thickness [70], road width [70], liquefier temperature [70], and air gap [67,69,70]. The overarching aim was to minimize dimensional variability [67], reduce build time [71] , enhance accuracy [71], refine surface roughness [70], and meticulously control porosity [70] in FDM parts.…”
Section: Genetic Algorithm (Ga)mentioning
confidence: 99%
“…Researchers use di erent optimization techniques like response surface methodology (RSM) [35], Taguchi method [36], full factorial [36] and fractional factorial [37], Gray relation [38], arti cial neural network (ANN) [39], fuzzy logic [40], genetic algorithm [41], and more others to optimize a number of the process parameters for improving tensile properties. It is also essential to be able to forecast how the parts will perform when applied to mechanical loads to assess their appropriateness for a given application.…”
Section: Previous Work and Analysis On The Optimization Of Fdm Proces...mentioning
confidence: 99%